2020
DOI: 10.1021/acs.jpcc.0c01372
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Charge-Transfer Character and Photoresponses of F4TCNQ-Based Donor–Acceptor Complexes

Abstract: F4TCNQ (2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane) is used widely as a hole-doping agent in photoresponsive organic semiconducting materials, yet relatively little is known about the photoresponses of the F4TCNQ·– anion generated via doping. Furthermore, there is still relatively little systematic exploration of how the properties of the local material or chemical environment impacts the driving force for generating these charge-transfer complexes. Here we present spectroscopic and photophysical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 63 publications
5
20
0
Order By: Relevance
“…The broad absorption from 650 to 950 nm is characteristic of the F 4 TCNQ anion; we also observe an additional broad feature above 950 nm, which we assign to the cation of the dendritic TPA. This is supported by previous electrochemical analysis of MPDA, which showed that the cation of the branched phenylenediamine has a broad absorption centered at 900 nm . In contrast, steady-state characterization of a mixture of MPDA and TCNE in dichloroethane (DCE), as shown in Figure S9, exhibited relatively little formation of CT complexes.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The broad absorption from 650 to 950 nm is characteristic of the F 4 TCNQ anion; we also observe an additional broad feature above 950 nm, which we assign to the cation of the dendritic TPA. This is supported by previous electrochemical analysis of MPDA, which showed that the cation of the branched phenylenediamine has a broad absorption centered at 900 nm . In contrast, steady-state characterization of a mixture of MPDA and TCNE in dichloroethane (DCE), as shown in Figure S9, exhibited relatively little formation of CT complexes.…”
Section: Resultssupporting
confidence: 76%
“…This is supported by previous electrochemical analysis of MPDA, which showed that the cation of the branched phenylenediamine has a broad absorption centered at 900 nm. 48 In contrast, steady-state characterization of a mixture of MPDA and TCNE in dichloroethane (DCE), as shown in Figure S9, exhibited relatively little formation of CT complexes. At the same concentrations used for the tricyanovinylation in DMF, we observe two different absorption features in DCE upon initial mixing of the reactants, one at 425 nm that corresponds to the TCNE anion 49 and another above 800 nm that corresponds to the MPDA cation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A weak shoulder at ∼480 nm was observed in the spectra of QPP-OMe/TCNQ and QPP-OMe/F 4 TCNQ, which may belong to a photoreaction product of the TCNQ or F 4 TCNQ with solvent molecules. 114,115 All TCNQ and QPP-OMe/F x TCNQ mixtures showed similar, strongly red-shifted charge-transfer bands, with a main peak close to the near-infrared region (λ max = 837−854 nm) and two other peaks of decreasing intensity at λ abs = 741− 753 nm and λ abs = 677−787 nm. These bands could not be seen, when measured in CH 2 Cl 2 or CHCl 3 , suggesting that the polarized charge transfer state is stabilized in the polar solvent MeOH.…”
Section: ■ Optoelectronic Propertiesmentioning
confidence: 96%
“…The charge transfer process (CT) has been extensively investigated in material science [1][2][3][4], biological systems [5,6], and crystal engineering [7,8]. The CT process is initiated between high electron donor molecules (Donors) and electron-deficient molecules (Acceptors) to form stable CT adducts [9,10].…”
Section: Introductionmentioning
confidence: 99%